Peluang dan Tantangan Santri di Era Digital (Studi Kasus Pada Pondok Pesantren Al Amin Sidoarjo) - Dhifan Hariz Kinansyah; Wahyu Eko Pujianto (Journal of Management and Social Sciences, 2023)
Digitizing Islamic boarding schools in Era Society 5.0 is an opportunity as well as a challenge for all Islamic boarding schools in Indonesia, apart from branding for their Islamic boarding schools, digitizing Islamic boarding schools also aims to inform the public that education is important. One of them is education at Islamic boarding schools as one of the printers of superior generations, especially in the fields of religion, self-reliance, manners, and social life. This study aims to describe the importance of digitizing education at the Al-Amin Sidoardjo Islamic Boarding School in the Era of Society 5.0. This research was conducted through a qualitative approach using descriptive analytic methods and included in field research. In Era Society 5.0, digital-based Islamic boarding school education is urgently needed, especially at the Al-Amin Sidoardjo Islamic Boarding School, which is still in the process of digital literacy. As for some of the efforts that have been made by the Al-Amin Sidoardjo Islamic Boarding School in digitizing, among others, by not conducting digital literacy training for students through graphic design courses so that students have IT competencies needed by the world of work and society, providing a computer laboratory with internet access for finding sources and references. religious and general knowledge that is difficult to access directly, and the use of websites and social media as a means of branding, dissemination of pesantren information dissemination, as well as pesantren administrative needs. Meanwhile, the challenges faced by the Al-Amin Sidoardjo Islamic boarding school are more in the unavailability of a special team of operators who are technically in charge both in terms of planning, organizing, implementing, and evaluating related to the pesantren's website and social media. In addition, the maintenance of digital systems and devices that are used for digitalization is not yet optimal.